A Historical and Contemporary Review of Questionnaires Used in the Management of Post-Radical Prostatectomy Patients. (23rd August 2022) - Cooper, Caleb A.; Sloan, Matthew J.; Singh, Armaan; Fantus, Richard J.; Raheem, Omer A.
Abstract: Introduction: Patients undergoing radical prostatectomy (RP) face obstacles to recovery spanning the domains of erectile and sexual function; urinary function; and health-related quality of life (HRQoL). Numerous patient-directed questionnaires exist that serve to assist in the care of these men. Aim: To describe patient-directed questionnaires of historical and contemporary relevance involving the evaluation and treatment of men after radical prostatectomy. Methods: A comprehensive review of peer-reviewed publications on the topic was performed. Using PubMed, the search terms used were: "radical prostatectomy; erectile function; lower urinary tract symptoms; sexual dysfunction; urinary incontinence; and health-related quality of life. Main Outcome Measure: We aimed to summarize questionnaires and survey devices of historical and contemporary importance for the care of men after RP. Results: Many questionnaires have been developed specifically for, or conscripted for use in, the care of men after RP. Some of the oldest questionnaires relating to sexual function, urinary function, and general and cancer-specific QoL are important and still utilized in the routine clinical care of post-RP patients. However, recent devices that may offer clinicians a more comprehensive understanding to aid in the evaluation and care of these men. Conclusions: Post-RP patients face numerous challenges that require a thoughtful approach, one that is broad enough to identify a variety of potential physical and emotional disturbances, yet granular enough to identify appropriate areas for intervention. While there is not a "best" questionnaire for this population, having an appropriate understanding of the current available instruments and what information they provide may help clinicians more thoroughly assess and treat these men.